Congruent and Incongruent Collocations of High-Frequency Verbs:: Do, Get, Give, Have, Make, Take - Chaimongkol, Thisakorn (Academic and Research Journal of Liberal Arts (Online), 2021)
This research aimed to explore which of the high-frequency verbs, do, get, give, have, make and take are congruent collocations with noun structures and which are incongruent collocations when translated into Thai and, to explore the characteristics of congruent collocations and incongruent collocations when translated into Thai. The research methodology, especially the analysis criteria for congruency and incongruency was adapted from Revier (2009), Jurko (2010) and Mustapic & Malenica (2013). The criteria used in this current study were divided into semantic parameters and structure parameters. The two resources used were, one month of news articles from the Bangkok Post and The Nation and previous delexical verbs related to the research were used as resources to find the target collocations with high-frequency verbs. All English-Thai translations equivalent meanings were translated and rechecked by two professional translators. The findings revealed that there were 397 collocations with high-frequency verbs found from the two resources. Congruent collocations accounted for 64.48 percent (256 collocations), whereas incongruent collocations accounted for 35.52 percent (141 collocations). Nouns which co-occur with high-frequency verbs in congruency tended to be deverbal nouns. As a result, the conclusion summarized in this study is in order to categorize which are congruent or incongruent collocations. The contrastive approach (translation between English-Thai) is a significant process to identify congruency and incongruency and is a learners’ strategy for collocation learning as mentioned in previous studies, therefore the objective criteria to make categorizations is even more necessary. Finally, the pedagogical implications proposed that the corpus of 397 congruent and incongruent collocations developed from this study would be used to produce key materials or data for collocation teaching.